A few exotic mycorrhizal fungi dominate eucalypts planted in England - Pennington,HG; Bidartondo,MI; Barsoum,N (Fungal Ecology, 2011)
Eucalypts have been planted widely outside of their native habitat for the purposes of commercial forestry. Mycorrhizal fungi are known to have spread with these trees around the world but little is known of the degree to which pre-existing mutualistic associations are maintained, or new associations are formed with Eucalyptus spp. outside of their native range. Molecular methods were used in this study to assess ectomycorrhizal communities colonising eucalypts in England. Our analyses revealed that only a dozen, mainly exotic, fungi were associated with eucalypts and that these mycorrhizal communities were dominated by a Laccaria sp. (C) 2011 Elsevier Ltd and The British Mycological Society. All rights reserved.